Pengaruh Pengetahuan Kewirausahaan terhadap Minat Berwirausaha Mahasiswa Prodi Pendidikan Guru dan Sekolah Dasar Univeritas Jambi - Nurdanti, Ulpi Romadhona; Damayanti, Gempita; Putra, Rian Arya; Adi, Emanuel Hosa Kurnia; Sofwan, Muhammad; Sholeh, Muhammad (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This research employs a descriptive quantitative approach with an explanatory survey method to explore the influence of entrepreneurship knowledge on entrepreneurial interest among PGSD (Elementary School Teacher Education) students at Universitas Jambi, Class of 2023. Data collection was conducted through questionnaires distributed to 34 respondents, representing 25% of the total student population. Data analysis included validity and reliability tests, classic assumptions, hypothesis testing, and multiple linear regression. The findings indicate that entrepreneurship knowledge, acquired through training and classroom learning, significantly influences entrepreneurial interest. The T-test reveals that the t-value (5.362) exceeds the critical t-value (2.036) with significance below 0.05, indicating a significant partial effect. The F-test demonstrates that entrepreneurship knowledge simultaneously affects entrepreneurial interest, with an F-value (28.754) surpassing the critical F-value (3.14) at a significance level below 0.05. Factors influencing entrepreneurial interest include enjoyment, curiosity, attention, and involvement. This study suggests enhancing more practical and interactive entrepreneurship programs to stimulate entrepreneurial interest among students.